Vpliv zasteklitve na energetsko učinkovitost montažnih lesenih stavb - Žegarac Leskovar, Vesna (Gradbeni vestnik, 2011)
The paper presents a numerical analysis of the increased proportion influence of glazing surfaces on energy efficiency of prefabricated timber single-familyhouses with a basic purpose to determine the influence of south oriented glazing area for new macro-panel wall elements of different thermal transmittances, as well as for old micro-panel wall elements, for which the installation of an optimal glazing size represents one of the possible energy efficient renovation methods. The research is based on a case study of a two-storey house and its parametric analysis of an increased-proportion-of-the-glazing-surfaces impact, taking into account the climate data for Ljubljana. As the result of the study, the annual energy demand for heating and cooling depending on the proportion of the glazing area in relation to the total surface area of the south oriented façade, under presumption that active systems are not changed, is presented. The results accord well with some findings of the existing parametrical analyses of different authors, while, on the other hand, they lead to some completely new findings regarding the optimal glazing share in south oriented external wall in dependence from the thermal transmittance of the wall element, considering climate data for Ljubljana.
Keywords: energetsko učinkovita gradnja; fasade; montažna gradnja; montažne hiše; zasteklitev